PENERAPAN KEGIATAN MENGGAMBAR BENTUK GEOMETRI DALAM UPAYA MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK USIA DINI - Ifadah, Ayunda Sayyidatul; Permata, Rista Dwi (Program Studi PG PAUD Universitas PGRI Ronggolawe, 2023)
This study aims to determine the increase in fine motor skills of early childhood aged 4-5 years through drawing activities with geometric blocks. This research is a Classroom Action Research (CAR) which was carried out on group A children at Dharma Wanita Kindergarten in Siding Village with a total of 27 research subjects. Data collection techniques using observation and documentation. In the initial conditions (pre cycle) it shows that the child's fine motor skills are still very low due to a lack of activities that stimulate fine motor skills and tend to focus more on activities that stimulate the child's cognitive. In the pre-cycle, data were obtained for 9 children who met the criteria for completion, 18 children who had not completed, and the percentage of class completeness was 33.3%. In cycle 1 there was an increase as many as 17 children were declared complete, 10 children had not completed, and the percentage of class completeness was 62.9%. Then in cycle 2 there was a significant increase where 24 children entered the criteria for completion, 3 children had not completed, and the percentage of class completeness increased to 88.8%.